EXPLORING ARYL-SUBSTITUTED 1,2,3-TRIAZOLES: SYNTHESIS, CHARACTERIZATION, AND THEORETICAL INVESTIGATIONS - Cesar Morales; Cristian Valdebenito; David Moreno da Costa; José Gaete; Alejandro Toro-Labbé; Karina Muñoz-Becerra; Gabriel Abarca (Journal of the Chilean Chemical Society, 2025)
This study synthesized newly designed 1,2,3-triazoles substituted with aryl groups via Sharpless' copper(I)-catalyzed azide-alkyne cycloaddition. The resulting compounds were extensively characterized using NMR and UV-Vis spectroscopy. Furthermore, theoretical DFT and time-dependent DFT calculations were performed to analyze the structural and electronic properties of these molecules. Computational analysis revealed insights into the electron distribution within these molecules, with the electron-withdrawing or electron-donating nature of the substituents affecting the HOMO-LUMO gap. These findings provide valuable information for tailoring the electronic properties of triazole-containing compounds, making them suitable for various chemical applications and potential coordination with metalloporphyrins.